Imperial ambitions : conversations on the post-9/11 world - Chomsky, Noam.; Barsamian, David ([S.l.] : Metropolitan Books, 2005)
In this first collection of interviews since the bestselling 9-11, our foremost intellectual activist examines crucial new questions of U.S. foreign policy Timely, urgent, and powerfully elucidating, this important volume of previously unpublished interviews conducted by award-winning radio journalist David Barsamian features Noam Chomsky discussing America$1 (Bs policies in an increasingly unstable world. With his famous insight, lucidity, and redoubtable grasp of history, Chomsky offers his views on the invasion and occupation of Iraq, the doctrine of (3z(Bpreemptive(3y (Bstrikes against so-called rogue states, and the prospects of the second Bush administration, warning of the growing threat to international peace posed by the U.S. drive for domination. In his inimitable style, Chomsky also dissects the propaganda system that fabricates a mythic past and airbrushes inconvenient facts out of history. Barsamian, recipient of the ACLU$1 (Bs Upton Sinclair Award for independent journalism, has conducted more interviews and radio broadcasts with Chomsky than has any other journalist. Enriched by their unique rapport, Imperial Ambitions explores topics Chomsky has never before discussed, among them the 2004 presidential campaign and election, the future of Social Security, and the increasing threat, including devastating weather patterns, of global warming. The result is an illuminating dialogue with one of the leading thinkers of our time$1 (Band a startling picture of the turbulent times in which we live.s